De l’apport du folk music revival au renouveau de l’accordéon diatonique en France et en Italie - Raffaele Pinelli (In Situ)
The rediscovery of the diatonic accordion, the "peasant instrument of the industrial age" in the words of Francesco Giannattasio, followed in the wake of the European revival movements, particularly in France and Italy. Thanks to the initiative of a number of musicians and instrument makers in both countries, the bellows instrument gradually came to the attention of the widest possible audience, evolving from a 'prototype' intended for the performance of repertoires of music in the oral tradition to an instrument in its own right, inspiring original music now composed for it. By examining the path taken by this instrument over the last few decades, the article looks at the facts and the inter-dynamic processes between certain musicians and instrument makers that have led, after several decades of low-intensity production, to both a revival of its instrument making and a renewal of its organology and repertoires.